Unusual presentation of cutaneous Leishmaniasis in pregnancy: A case report - Radia Chakiri; Salim Gallouj; Fatima Zohra Mernissi; Mouna Rimani (Our Dermatology Online, 2017)
Cutaneous Leishmaniasis is a parasitic infection characterized by significant clinical variability. Unusual and atypical clinical aspects of infection have been reported in immunodeficient patients or associated with particular parasite species. We report a pregnant woman with unusual presentation of cutaneous Leishmaniasis.